Children infected vs. uninfected with COVID-19: Differences in parent reports of the use of mobile phones to calm children, routines, parent–child relationship, and developmental outcomes - Lau, Eva Yi Hung; Li, Jian-Bin; Chan, Derwin King Chung (Frontiers in Public Health, 2023)
Children were suggested to be at lower risk of developing the severe form of the COVID-19. However, children infected with COVID-19 may be more likely to experience biopsychosocial stressors associated with the pandemic and display poorer developmental outcomes. The current study is among the first to compare children infected and uninfected with COVID-19 on outcomes related to parents' use of mobile phones to calm children, routines, parent‒child relationship, externalizing and internalizing problems, prosocial behavior, gratitude, and happiness. A total of 1,187 parents (88.6% mothers) of children aged 5 to 12 completed an online survey between April 2022 and May 2022 when schools were suspended during the 5th wave of resurgence in Hong Kong. Our findings showed no substantial differences in various psychological, social, emotional, and behavioral outcomes between infected and uninfected children. Our findings can be used to educate parents to reduce their fear and anxieties associated with their children's COVID-19 infection. Our findings also suggested that support during the pandemic should be provided to children and families regardless of whether children have been infected with COVID-19.